Public Perceptions of Service Dogs, Emotional Support Dogs, and Therapy Dogs - Schoenfeld-Tacher, Regina (Int J Environ Res Public Health, 2017)
As service dogs, emotional support dogs, and therapy dogs have become more prevalent in the USA, so too has the controversy surrounding their legitimacy. Yet, there is a lack of objective data regarding the public’s understanding of the role played by each of these types of animals, as well as their perceptions regarding the legitimacy of their integration. An anonymous, online survey was distributed to examine the perceptions of US adults who do not own any type of assistance animal. A total of 505 individuals responded to the online survey, yielding 284 usable responses. Results suggest widespread misconceptions about definitions, rules, regulations, and rights associated with each type of assistance dog. In general, service dogs are more likely to be perceived as helping with a legitimate need, and their access to public spaces is viewed favorably. While there are some concerns about the legitimacy and necessary access rights for emotional support dogs, members of the public correctly identified the roles and rights of therapy dogs. Despite the media’s focus on abuses and false representation of these dogs, most participants reported feeling the majority of people are not taking advantage of the system.